2019
DOI: 10.1055/s-0039-1684037
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Use of Analgesics in Tonsillar Fossa and Postoperative Evaluation with Visual analogue Scale Scores—A Prospective, Randomized, Placebo-Controlled, Double-Blind Clinical Trial

Abstract: Introduction  Posttonsillectomy pain results in significant morbidity to the patients. There is a disagreement in the literature regarding the use of local anesthetics during tonsillectomy. The aim of this placebo-controlled, double-blind study is to evaluate the effect of peritonsillar administration of local anesthetics. Objective  To evaluate the role of intraoperative use of analgesics in tonsillar fossa and postoperative evaluation with visual analogue scale (VAS) scores in achieving pain relief after to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…Of these, 379 patients (122 females and 167 males) received bupivacaine and 331 patients (130 females and 141 males) received normal saline (control group). Furthermore, two studies did not define or mention the patients' sex distributions ( 28 , 30 ). The mean age of all the patients was 9.1±5.6 years.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of these, 379 patients (122 females and 167 males) received bupivacaine and 331 patients (130 females and 141 males) received normal saline (control group). Furthermore, two studies did not define or mention the patients' sex distributions ( 28 , 30 ). The mean age of all the patients was 9.1±5.6 years.…”
Section: Resultsmentioning
confidence: 99%
“…The mean age of the patients in the bupivacaine and the control group was 9.1±6.4 and 8.8±4.9 years, respectively. However, two studies reported only the overall mean age of their sample ( 28 , 30 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations